A Trying Balance: Determining the Trier of Fact in Hybrid Admiralty-Civil Cases - Lily Kurland (Washington University Law Review, 2013)
Although admiralty is among the law’s oldest practices, it continues to play a vital role in modern litigation—whether that be through the transportation of goods on rivers or people on cruise ships. Prior to 1966, a federal court exercising its admiralty jurisdiction relied on a different set of rules than when it acted in law or equity.To accommodate this distinction, cases were placed on separate dockets based on the court’s source of jurisdiction. This system resulted in procedural differences that set admiralty claims apart from others. Admiralty cases were historically tried before the bench, while common law claims, as protected by the Seventh Amendment, were tried before a jury. In an effort to modernize admiralty law and prevent the dismissal of valid claims for procedural technicalities, the admiralty and civil dockets were unified in 1966. “The resulting joinder provisions of the Federal Rules of Civil Procedure apply to all cases and make it possible to join both admiralty and nonadmiralty claims in a single action.” These cases are treated as hybrid admiralty- civil cases. While the 1966 unification corrected many of the dual-docket difficulties, it created two new problems of its own. First, should a judge or jury determine the facts in a hybrid admiralty-civil case when each claim has an independent basis for federal jurisdiction? Second, should the court undertake a separate analysis to determine the fact-finder in a hybrid case when the civil claim does not have an independent basis for federal jurisdiction? If so, what should this analysis look like and which trier of fact should determine the case outcome? The Supreme Court has failed to answer these questions, leaving the circuits split. This Note analyzes and evaluates the conflict among courts for both of these questions. Part I introduces the current conflict among circuits. Part II presents a general history of admiralty courts and law with an emphasis on its international development as a separate body of courts and its procedure before and after the 1966 unification. Part III explores the three approaches adopted by courts in determining the trier of fact when both the admiralty and civil claims have independent bases for federal jurisdiction. Part IV examines the approaches adopted by courts in determining the trier of fact when the civil claim does not have an independent basis for federal jurisdiction. Part IV, utilizing the approach adopted by many courts, separates those claims involving limitation of liability proceedings from those without such an action. Part V analyzes the conflict among the courts and proposes an answer to each of the two questions above. When each claim comprising a hybrid admiralty-civil case has an independent basis for federal jurisdiction, the court should attempt to sever the claims so as to preserve the common law jury right and the admiralty bench trial. If the facts of the claims are so intertwined as to make severance impossible, the civil litigant’s jury right must trump the traditional admiralty bench trial. When the civil claim in a hybrid case does not have an independent basis for federal jurisdiction, the traditional admiralty bench trial should be preserved in all but one situation—when the civil litigant is forced into federal court through the initiation of a limitation of liability proceeding.
Keywords: admiralty; trier of fact